Dorsolateral Biplane Closing Radial Osteotomy and Lunate Fixation for Stage IIIC Kienböck Disease: A New Surgical Approach. Issue 3 (September 2018) - Barrera-Ochoa, Sergi; Campillo-Recio, David; Muñoz-Perdomo, Tryno; Esteban-Feliu, Ignacio; Mendez-Sanchez, Gerardo; Mir-Bullo, Xavier
Abstract : The treatment of advanced-stage Kienböck disease (KD) remains highly controversial. Particularly important is stage IIIC KD, which includes patients with a lunate coronal fracture. The purpose of this paper was to describe a new approach to KD in patients with Lichtman stage IIIC KD, and our results using it. The procedure combines a dorsolateral biplane closing radial osteotomy and lunate fixation. A total of 11 patients from January 2002 through December 2016 with documented KD who underwent this technique were included. The patients were assessed before surgery, then postoperatively at 1 and 10 days, 3 and 6 weeks, 3 and 6 months, and annually. Wrist range of motion, grip and pinch strength, the Quick Disabilities of the Arm, Shoulder and Hand (QuickDASH) score, a Modified Mayo Wrist Score (MMWS), 10-point visual analog scale, radiologic measurements, and data related to consolidation were collected. All statistical analyses were performed using the statistical software package SPSS. Some degree of pain relief, improvements in the QuickDASH score, MMWS score, grip strength, and the degrees of flexion and extension were observed, the results being statistically significant ( P <0.05). After surgery, the values for radial and sagittal tilt were statistically different than those measured before surgery. Carpal collapse was not evident either before or after surgery. In conclusion, combining a dorsolateral radial osteotomy and a lunate compression screw may expand the options for patients with Lichtman stage IIIC KD. Our experience indicates that it is a viable option in challenging clinical scenarios.